Africa's Prospects for Enjoying a Demographic Dividend - David E. Bloom; Michael Kuhn; Klaus Prettner (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2016)
We assess Africa's prospects for enjoying a demographic dividend. While fertility rates and dependency ratios in Africa remain high, they have started to decline. According to United Nations projections, they will fall further in the coming decades such that by the mid-21st century the ratio of the working-age to dependent population will be greater than in Asia, Europe, and Northern America. This projection suggests Africa has considerable potential to enjoy a demographic dividend. Whether and when it actually materializes, and also its magnitude, hinges on policies and institutions in key realms that include macroeconomic management, human capital, trade, governance, and labour and capital markets. Given strong complementarities among these areas, coordinated policies will likely be most effective in generating the momentum needed to pull Africa's economies out of a development trap.
Keywords: 300; Africa; declining fertility; demographic dividend; development; education; health; infrastructure